The Effect of Service Quality on Customer Loyalty with Brand Trust as an Intervening Variable in NDC Dental Clinic - Agustin, Nina (Universitas Ciputra Surabaya, 2023)
This study aims to examine the effect of service quality on customer loyalty with brand trust as an intervening variable at the NDC Dental Clinic. The variables studied were Service Quality (X), Brand Trust (Z), and Consumer Loyalty (Y). Service Quality has five indicators, namely Tangible, Reliability, Responsiveness, Empathy and Assurance. Brand Trust has three indicators, namely Trust in the brand, Security of a brand, and Honesty of a brand. Customer loyalty has four indicators, namely making repeat purchases, recommending products to others, buying between product and service lines, and not being influenced by other products. The analytical tool used is analysis using SEM-PLS. The population in this study is the data of 120 people taken from patients with purposive sampling technique. The results of this study indicate that the service quality variable has a significant effect on brand trust. The brand trust variable has a significant effect on customer loyalty. Service quality variable has a significant effect on customer loyalty. And the service quality variable has a significant effect on customer loyalty through brand trust.